Strategy for Disaster Adaptation to Improve Student Resilience in Schools: A Systematic Review - Nur Hafida, Siti Hadiyati; Mohd Isa, Nor Kalsum; Jumadi, .; Ibrahim, Mohd Hairy Bin (GEOGRAFI, 2021)
For several years, disaster-related studies have always focused on disaster preparedness and risk reduction efforts. Researchers also attribute disasters more to the context of society, even though schools are one of the most vulnerable places to catastrophe. Many schools are located in disaster-prone areas, and children spend most of their time in school. This study aims to identify strategies to improve disaster adaptation capacity in schools. This study used a database from Sciencedirect, Springerlink, Taylor & Francis, and Emerald with the keywords “adaptation”, “disaster”, “children”, “strategy”, and “school”. There were 7,230 articles in total related to these keywords, and only 21 articles were selected. The remaining articles were unselected due to a less relevant stance to the topic of this study. Thematic analysis techniques were used in the process of analysing reports. The thematic analysis results show that there are five main strategies in improving disaster capacity in schools, that is increasing access to assets, flexibility and diversity, social ability, learning integration, and organizational development. From these five strategies, 25 sub-strategies were obtained to support the achievement of disaster adaptation. The government needs to pay more attention to the schools’ condition in disaster-prone areas and implement disaster adaptation strategies in schools. The ability of disaster adaptation can encourage the school community to be well-prepared in overcoming disasters.